Temperature Dependence of the Tilt Angle for the Smectic A-Smectic Transition in a Mixture of C7-70PDOB Ferroelectric Liquid Crystals near the Tricritical Point - Mustafa Kurt; Hamit Yurtseven (Advances in Condensed Matter Physics)
The temperature dependence of the tilt angle is studied in the smectic phase near the smectic A-smectic tricritical point for a mixture of 70PD0B in the ferroelectric liquid crystal C7 (). The mean-field models with the biquadratic ( is the spontaneous polarization) and (bilinear) coupling terms in the free energy expansion are used to analyze the experimental data for the tilt angle in this binary mixture. From our analysis, the coefficients given in the free energy expansion of the mean-field models are determined. Our results show that the mean-field theory explains adequately the observed behaviour of the C7-70PD0B mixture near the tricritical point.